SIGGRAPH Asia 2019 Posters 2019
DOI: 10.1145/3355056.3364590
|View full text |Cite
|
Sign up to set email alerts
|

Method for estimating display lag in the Oculus Rift S and CV1

Abstract: We validated an optical method for measuring the display lag of modern head-mounted displays (HMDs). The method used a high-speed digital camera to track landmarks rendered on a display panel of the Oculus Rift CV1 and S models. We used an Nvidia GeForce RTX 2080 graphics adapter and found that the minimum estimated baseline latency of both the Oculus CV1 and S was extremely short (~2 ms). Variability in lag was low, even when the lag was systematically inflated. Cybersickness was induced with the small baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 5 publications
0
24
3
Order By: Relevance
“…Research has shown that imposing an additional constant lag into the system increases the likelihood and severity of cybersickness (DiZio and Lackner, 1997;Jennings et al, 2000Jennings et al, , 2004Caserman et al, 2019;Feng et al, 2019;Palmisano et al, 2019;Kim et al, 2020). While a small number of studies have failed to find such effects (Draper et al, 2001;, we note that the baseline lags of their systems were already quite high (∼40-70 ms).…”
Section: Effects Of Adding Constant Display Lag On Cybersicknessmentioning
confidence: 51%
See 4 more Smart Citations
“…Research has shown that imposing an additional constant lag into the system increases the likelihood and severity of cybersickness (DiZio and Lackner, 1997;Jennings et al, 2000Jennings et al, , 2004Caserman et al, 2019;Feng et al, 2019;Palmisano et al, 2019;Kim et al, 2020). While a small number of studies have failed to find such effects (Draper et al, 2001;, we note that the baseline lags of their systems were already quite high (∼40-70 ms).…”
Section: Effects Of Adding Constant Display Lag On Cybersicknessmentioning
confidence: 51%
“…While the above example is focused on user head rotation in pitch, our research suggests that head rotations in yaw (and presumably also in roll) can generate provocative DVP during HMD VR (Feng et al, 2019;Palmisano et al, 2019). During each of these head rotations, DVP will increase in magnitude and become more variable when: (1) additional (constant or time-varying) display lag is injected into the system; and (2) the user's head-movement speed increases.…”
Section: A Hypothesis Specifically Developed For Cybersickness In Hmd Vrmentioning
confidence: 88%
See 3 more Smart Citations